(untitled) (Journal of Oriental Studies, 2025)
This article examines the semantic and syntactic application of the verb جعل (jaʿala) based on data from Quranic texts and classical Arabic dictionaries. The analysis suggests the existence of several meanings for the verb جعل (jaʿala), encompassing creating, making, placing, imposing, naming, and other functions, depending on the number of objects the verb requires in a sentence. Generalizing the obtained data, the study concludes that the verb جعل (jaʿala) is used with the meaning of "to create" or "to make" when it requires one object, and sometimes appears as a tool for transformation or attribution when it requires two or more objects. This analysis is an important contribution to the grammatical and syntactic study of Arabic, allowing for a deeper understanding of those verses in the Quran where the verb is used.